1999
DOI: 10.1046/j.1365-2249.1999.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of B7.2 and B7.1 on B cells by immunosuppressive agents

Abstract: Several recent studies demonstrate that B7.2, but not B7.1, play an important role in allergic inflammation and IgE production. Agents that down-regulate B7.2 may therefore be of benefit for the treatment of Th2-driven allergic diseases. Our current study was carried out to investigate the effect of immunosuppressive agents, cyclosporin A (CsA) and dexamethasone, on B7.2 and B7.1 expression on B cells stimulated with the superantigen, toxic shock syndrome toxin-1 (TSST-1). The analysis of B7.2 and B7.1 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Although IL-4 is necessary for IgE isotype switching, it is not sufficient. For IgE secretion to occur, a second signal mediated by cell-cell T and B cell interactions via CD40L-CD40 and CD28-CD86 ligand-receptor interactions is needed [115][116][117][118][119][120][121][122][123][124][125][126][127]. IL-4 also induces the lowaffinity IgE receptor CD23 and soluble CD23, which augments B cell IgE synthesis [115,116,[128][129][130][131][132][133].…”
Section: Immunopathogenesis Of Abpa In Cfmentioning
confidence: 99%
“…Although IL-4 is necessary for IgE isotype switching, it is not sufficient. For IgE secretion to occur, a second signal mediated by cell-cell T and B cell interactions via CD40L-CD40 and CD28-CD86 ligand-receptor interactions is needed [115][116][117][118][119][120][121][122][123][124][125][126][127]. IL-4 also induces the lowaffinity IgE receptor CD23 and soluble CD23, which augments B cell IgE synthesis [115,116,[128][129][130][131][132][133].…”
Section: Immunopathogenesis Of Abpa In Cfmentioning
confidence: 99%
“…It has been found that CsA can also influence functions of other immune cells, including natural killer (NK) cells, macrophages, as well as dendritic cells (Wasowska et al 2001, Sauma et al 2003, Chen et al 2004, Poggi & Zocchi 2005. CsA even modulates the expression of two crucial costimulatory molecules, CD80 and CD86, which are pivotal in the induction of the alloantigen-specific tolerance (Sayegh & Turka 1995, Jirapongsananuruk & Leung 1999, Lee et al 1999. The clinical application of CsA has revolutionized organ transplantation and also improved the therapeutic management of some autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of the CsA effect was shown to be exhibited by virtue of interfering with the intracellular calcineurin pathway of T cells 9 . On the other hand, a line of evidence has suggested recently that CsA exerts its immunological functions not only on T cells but also on antigen‐presenting cells such as B cells, 10 macrophages 11 and dendritic cells (DCs) 12,13 …”
Section: Introductionmentioning
confidence: 99%